Resistors and Humidity Sensors
Patent Information
- Application Number
- JP2021088262
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-05-26
AI Technical Summary
【0016】 本発明の抵抗体は、セルロースナノファイバーが水分を吸収して膨潤することにより、カーボン粒子を含有する抵抗体全体の導電率が変化し、その鋭敏な感応性により、湿度の測定が可能である。
Smart Images

Figure 0007641626000001 
Figure 0007641626000002 
Figure 0007641626000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resistor suitable for use as a humidity sensor. [Background technology]
[0002] Humidity sensors are important in a variety of fields, from environmental measurement to agriculture and logistics, and recently they have been highly anticipated for use in healthcare for continuous respiratory monitoring. Humidity sensors are known to be of the capacitive and resistive types, but capacitive types are difficult to miniaturize and are not suitable for wearable devices.
[0003] Resistance-changing humidity sensors are known that use hydrophilic polymers as moisture-sensitive materials and have a structure that bridges between electrodes, and can electrically measure the humidity of the moisture-sensitive material to measure humidity. It is also known that moisture-sensitive materials with conductive particles dispersed therein exhibit resistance changes in response to changes in the surrounding humidity. For example, composite materials using fibers (such as cellulose) and carbon nanotubes in the moisture-sensitive layer have been reported (Non-Patent Documents 1-2). These composite materials are resistance-changing, can be easily manufactured, and have excellent flexibility. However, carbon nanotubes are very expensive. In addition, it is difficult to disperse them uniformly in the composite material.
[0004] Also, a moisture-sensitive resistor has been reported in which carbon is added as conductive particles to a moisture-sensitive material such as a polyvinyl alcohol polymer, a polyvinyl alcohol polymer and a cellulose derivative polymer, a saponified polymethyl acrylate, or a saponified polyethyl acrylate (Patent Document 1). This type of structure is simple and can be mass-produced, so it can be manufactured relatively inexpensively.
[0005] However, these humidity-sensitive resistors still have problems with responsiveness, reproducibility, hysteresis, and the like, because the conductive particles in the resin move every time the humidity detection history is repeated. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 59-114452 [Non-patent literature]
[0007] [Non-Patent Document 1] P.Zhu et al. Applied Materials & Interfaces 2020, 12, 33229 [Non-Patent Document 2] M. Parrilla et al. Adv. Healthcare Mater. 2019, 1900342 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to provide a resistor for a humidity sensor, which is made of a composite material of cellulose nanofibers that swell with moisture and conductive carbon particles, and a humidity sensor using the resistor. [Means for solving the problem]
[0009] The present invention comprises the following: [1] A resistor comprising cellulose nanofibers and carbon particles dispersed among the cellulose nanofibers, having electrical conductivity, the electrical conductivity of which changes in response to moisture.
[0010] [2] The resistor according to [1], characterized in that the content of the carbon particles relative to the cellulose nanofibers is a mass ratio of 0.2 to 10.
[0011] [3] The resistor according to [1] or [2], wherein the carbon particles are carbon black.
[0012] [4] The resistor according to any one of [1] to [3], further comprising a surfactant in addition to the cellulose nanofibers and carbon particles.
[0013] [5] The resistor according to any one of [1] to [4], wherein the cellulose nanofibers have a fiber diameter of 1 to 10 nm and a fiber length of 100 nm to 10 μm.
[0014] [6] The resistor according to any one of [1] to [5], characterized in that when placed in an environment with a relative humidity of 40% to 90% RH, the resistance value changes by 100% or more within 30 seconds.
[0015] [7] A humidity sensor comprising: a pair of electrodes formed on a substrate; and the resistor according to any one of [1] to [6] formed between the pair of electrodes. Effect of the Invention
[0016] In the resistor of the present invention, the cellulose nanofibers absorb moisture and swell, changing the electrical conductivity of the entire resistor containing the carbon particles, and this keen sensitivity makes it possible to measure humidity. [Brief description of the drawings]
[0017] [Figure 1] 1(a) and (b) are SEM images of cellulose nanofibers and their enlarged images, FIG. 1(c) and (d) are SEM images of resistor CB0.2 (Example 3) and their enlarged images, and FIG. 1(e) and (f) are SEM images of resistor CB1 (Example 1) and their enlarged images.
[0018] [Diagram 2]FIG. 2(a) is a graph showing the relationship between the relative humidity (%RH) and the resistance change rate (R / R0) of resistor CB1 (Example 1), resistor CB0.5 (Example 2), resistor CB0.2 (Example 3), and resistor CB2 (Example 4). FIG. 2(b) is a graph showing the relationship between the relative humidity (%RH) and the resistance change rate (R / R0) of resistor TX0.25 (Example 5) and resistor TX0.5 (Example 6). FIG. 2(c) is a graph showing the relationship between the relative humidity (%RH) and the resistance change rate (R / R0) of five devices of resistor CB0.2 (Example 3). FIG. 2(d) is a graph showing the relationship between the time (seconds) and the resistance change rate (R / R0) when resistor CB0.2 (Example 3) is placed in an environment with a relative humidity of 30% RH, then 80% RH, and again 30% RH in that order. Fig. 2(e) is a graph showing the resistance change rate (R / R0) of resistor CB0.2 (Example 3) when it is repeatedly placed in environments with relative humidity of 30% RH and 80% RH in turn. Fig. 2(f) is a graph showing the relationship between time (seconds) and the resistance change rate (R / R0) when resistor CB0.2 (Example 3) is placed in environments with relative humidity of 40% RH, then 90% RH, and again 40% RH in turn. In Fig. 2(a) to (f), the vertical axis R / R0 represents the measured resistance value (R) relative to the resistance value (R0) at 30% RH.
[0019] [Diagram 3] Fig. 3(a) is a graph showing the resistance change rate (R / R0) when resistor CB0.2 (Example 3) is placed in an environment where the humidity is fixed at 50% RH and only the temperature is changed to 25° C., 35° C., and 45° C. Fig. 3(b) is a graph showing the relationship between the bending radius (mm) of resistor CB0.2 (Example 3) and the resistance change rate (R / R0).
[0020] [Figure 4] 1A to 1C are diagrams showing the process of producing a humidity sensor using a resistor of the present invention. [Diagram 5] FIG. 5 is a graph showing the relationship between the relative humidity (% RH) and the resistance change rate (R / R0) of resistor GNP2 (Example 8), resistor GNP3 (Example 9), resistor GNP5 (Example 10), and resistor GNP10 (Example 11). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The resistor and humidity sensor of the present invention will be described in detail below. The resistor of the present invention contains cellulose nanofibers that swell with moisture and carbon particles dispersed among the cellulose nanofibers. The resistor is conductive and changes its conductivity when it absorbs moisture. That is, when the cellulose nanofibers absorb moisture, the resistor swells, changing the distance between the dispersed carbon particles and cutting the conductive path, decreasing the conductivity and increasing the resistance value.
[0022] Cellulose nanofibers are cellulose fibers that have been finely pulverized to the nano-order. The fiber diameter is preferably 1 to 10 nm, and the fiber length is preferably 100 nm to 10 μm. The cellulose nanofibers having such extremely fine fibers form a three-dimensional network in the resistor, and many hydroxyl groups of hydrophilic groups that constitute cellulose are evenly dispersed throughout the network. For this reason, the resistor formed from the cellulose nanofibers is easy to capture moisture, and the entire resistor is in a state in which it has absorbed moisture in the air. In addition, by forming the resistor into, for example, a thin film, the amount of moisture in the resistor can be changed in a short time to a moisture amount corresponding to the moisture in the air, even if the amount of moisture in the air fluctuates, that is, the humidity changes.
[0023] As the cellulose nanofibers, for example, commercially available products such as Rheocrysta (registered trademark; fiber diameter 3 nm, fiber length approximately 1000 nm; manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) are used.
[0024] For the carbon particles, conductive fine particles such as carbon black, graphene, and multi-layer graphene (graphite) are used. For graphene and graphite, it is preferable to use graphite materials that are thinned to nano-size, so-called nanoplatelets. Of the carbon particles, carbon black is preferable because it is less prone to deterioration of conductivity due to moisture absorption, etc. Carbon black is easily dispersed in cellulose nanofibers. This is because the fiber diameter of cellulose nanofibers is about 1 / 10 the particle diameter of carbon black. It is also very inexpensive and an environmentally friendly material. For carbon black, for example, commercially available products such as Ketjen Black (manufactured by Lion Specialty Chemicals Co., Ltd.) are used.
[0025] In the resistor of the present invention, carbon particles are uniformly dispersed in the cellulose nanofiber, and the cellulose nanofiber and the carbon particles are integrated by the bonding function of the hydrophilic groups of the cellulose nanofiber. The carbon particles function to change the electrical resistance value. In other words, when the cellulose nanofiber absorbs moisture in the air, the carbon particles respond sensitively to this and exhibit humidity detection capabilities.
[0026] The ratio of cellulose nanofibers and carbon particles in the resistor can be set as appropriate, but the content of carbon particles is preferably 0.2 to 10 parts by mass, more preferably 0.2 to 2 parts by mass, and particularly preferably 0.2 to 0.5 parts by mass, per 1 part by mass of cellulose nanofibers. However, when the carbon particles are carbon black, the content of the carbon particles is particularly preferably 0.2 to 0.5 parts by mass per 1 part by mass of carbon black. However, when the carbon particles are graphene nanoplatelets, it is preferable to add more of them than carbon black, more preferably 2 to 5 parts by mass.
[0027] The resistor is produced by adding carbon particles to an aqueous dispersion of cellulose nanofibers, stirring and mixing to disperse the carbon particles uniformly, and then removing the solvent.
[0028] The solvent for the resistor is water or an organic solvent, or a mixture of water and an organic solvent, such as, but not limited to, ethanol, methyl ethyl ketone, ethylene glycol, and glycerin.
[0029] When the carbon particles are added to the aqueous dispersion of cellulose nanofibers and stirred to disperse uniformly, a surfactant may be added as necessary. The surfactant may be either an ionic surfactant (anionic surfactant, cationic surfactant, amphoteric surfactant) or a nonionic surfactant. In particular, it is preferable to use a nonionic surfactant such as polyoxyethylene alkylphenyl ether or an acrylic emulsion (Triton X-100; manufactured by Sigma-Aldrich).
[0030] The amount of surfactant added is usually 0.25 to 1 part by mass, and preferably 0.3 to 0.5 parts by mass, per part by mass of cellulose nanofibers. The sensitivity of the humidity sensor can be increased by adding a surfactant. If the mass ratio of surfactant to cellulose nanofiber is less than 0.25, the effect is small and the printing performance decreases. On the other hand, if the surfactant is added in a ratio exceeding 1, the resistance value of the resistor becomes high, which is detrimental.
[0031] The resistor responds quickly to changes in the surrounding humidity, and preferably changes in resistance by 100% or more within 30 seconds when placed in an environment where the relative humidity is changed from 30% to 90%.
[0032] The humidity sensor of the present invention comprises a pair of electrodes formed on a substrate, and the resistor formed between the pair of electrodes. The substrate is usually an insulating plastic film or paper having a thickness of 10 to 300 μm. Examples of the plastic film include, but are not limited to, polyimide film, polyethylene terephthalate film, and polyethylene naphthalate (PEN). It is not necessary to use a substrate. In the humidity sensor, the resistor has a thickness of 0.1 to 25 μm and is usually formed in a square or rectangular shape with one side measuring 3 to 20 mm, but is not limited to this and may be a circular or other irregular shape.
[0033] As shown in Figures 4(a) to (d), the humidity sensor is produced by forming a pair of electrodes by printing an electrode ink or depositing an electrode material on a substrate using a mask having openings in a shape corresponding to the electrode pattern, and then forming the resistor so as to straddle both electrodes of the pair of electrodes using a mask having openings in a shape corresponding to the resistor.
[0034] The electrode pattern is formed by printing or deposition. When printing, flexographic printing, screen printing, inkjet printing, gravure printing, etc. are used. When deposition is performed, chemical vapor deposition (CVD) or physical vapor deposition (PVD) is used.
[0035] The humidity sensor obtained as described above has a resistance value of 1 kΩ to 1 MΩ at 30% RH. The humidity sensor is suitable for various applications such as a contactless switch, a proximity sensor, and a water detection sensor, but since it is particularly light, thin, and flexible, it is also highly compatible with humans and is also suitable as a breathing sensor incorporated into a mask, a sweat sensor, a wetness sensor for diapers, etc. EXAMPLES
[0036] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to the following examples.
[0037] [Example 1] Cellulose nanofibers (LeoCrysta (registered trademark), fiber diameter 3 nm, fiber length approximately 1000 nm, Daiichi Kogyo Seiyaku Co., Ltd.) were diluted to 1 wt% with ultrapure water, and carbon black (Ketjen Black, Lion Specialty Chemicals Co., Ltd.) and surfactant (nonionic surfactant Triton TX-100, purchased from Sigma-Aldrich Co., Ltd.) were added to this cellulose nanofiber (1 wt%, 500 mg) solution so that the ratio of cellulose nanofiber:carbon black:surfactant was 1:1:0.5 (mass ratio), and the mixture was stirred for 5 minutes and degassed for 2 minutes using a stirring and degassing machine (Thinky Corporation, Mixer AR-100) to prepare resistor (CB1) ink. On the other hand, an electrode pattern was formed on a polyethylene naphthalate (PEN, DuPont) film with a thickness of 100 μm using Ag paste (XA-3609, Fujikura Kasei Co., Ltd.) with a screen printer (Microtec Co., Ltd.), and the film was heated and cooled in air at 130° C. for 30 minutes. Then, using a resistor formation mask, the resistor (CB1) ink was stencil-printed on the electrodes, and the film was heated and cooled on a hot plate at 120° C. for 5 minutes to prepare a humidity sensor. SEM images of the resistor part (resistor (CB1)) of the humidity sensor and its enlarged image are shown in Figure 1(e) and (f). It can be seen that the carbon black is uniformly dispersed in the cellulose nanofibers, forming a fibrous, porous conductive network.
[0038] [Example 2] A resistor (CB0.5) was produced in the same manner as in Example 1, except that the ratio of the cellulose nanofibers, carbon black, and nonionic surfactant in Example 1 was 1:0.5:0.5 (mass ratio). A humidity sensor was produced in the same manner as in Example 1.
[0039] [Example 3] A resistor (CB0.2) was produced in the same manner as in Example 1, except that the ratio of the cellulose nanofibers, carbon black, and nonionic surfactant in Example 1 was 1:0.2:0.5 (mass ratio). A humidity sensor was produced in the same manner as in Example 1. From the SEM images in Figure 1(c) and (d), it can be seen that the carbon black is uniformly dispersed in the cellulose nanofibers, forming a fibrous porous network.
[0040] [Example 4] A resistor (CB2) was produced in the same manner as in Example 1, except that the ratio of the cellulose nanofibers, carbon black, and nonionic surfactant in Example 1 was 1:2:0.5 (mass ratio). A humidity sensor was produced in the same manner as in Example 1.
[0041] For the humidity sensors of Examples 1 to 4, the relative humidity (% RH) and the resistance change rate (R / R 0 The humidity sensor of Example 3 was particularly excellent in humidity sensitivity. 0 is the resistance value at 30% RH (R 0 It represents the ratio of the measured resistance (R) to the measured value of resistance (R).
[0042] FIG. 2(c) shows the resistance change rate (R / R 0 The characteristics of all five devices are nearly identical, with little variation and accurate reproduction. From the graph in FIG. 2(d), when the humidity sensor of Example 3 was placed in an environment with a relative humidity of 30% RH, then 80% RH, and then 30% RH again, the response speed when moved from 30% RH to an 80% RH environment was about 10 seconds, and the response speed when moved from 80% RH to 30% RH was about 6 seconds. From this result, it can be seen that the response speed of the humidity sensor of the present invention is very fast. In addition, the resistance change rate (R / R0 ) was constant (Figure 2(e)). With the humidity sensor of Example 3, the time required for the resistance value to change by 100% or more in response to an environmental change in relative humidity from 40% RH to 90% RH was 30 seconds or less (FIG. 2(f)). Since such a high-speed response is possible, it is possible to apply the sensor to, for example, a non-contact proximity sensor or a respiration sensor.
[0043] The graph in FIG. 3(a) shows the resistance change rate (R / R 0 ) represents the rate of resistance change (R / R 0 ) was almost constant, and this humidity sensor had very little dependence on temperature and only dependence on humidity. The graph in FIG. 3(b) shows the relationship between the bending radius (mm) and the resistance change rate (R / R 0 ) and indicates that there is no change in the rate of resistance change even when the sensor is bent. This shows that the humidity sensor of the present invention can be used in curved locations and is a device with excellent flexibility.
[0044] [Example 5] A resistor (TX0.25) was produced in the same manner as in Example 3, except that the ratio of the cellulose nanofibers, carbon black, and nonionic surfactant in Example 3 was 1:0.2:0.25 (mass ratio). A humidity sensor was produced in the same manner as in Example 1.
[0045] [Example 6] A resistor (TX0.5) was produced in the same manner as in Example 5, except that the ratio of the cellulose nanofibers, carbon black, and nonionic surfactant in Example 5 was 1:0.2:0.5 (mass ratio). Note that TX0.5 has the same composition as CB0.2 in Example 3. A humidity sensor was produced in the same manner as in Example 1.
[0046] Between the humidity sensors of Examples 5 and 6, the sensor of Example 6 had superior humidity sensitivity (FIG. 2(b)).
[0047] [Example 7] A resistor (TX1) was produced in the same manner as in Example 5, except that the ratio of the cellulose nanofibers, carbon black, and nonionic surfactant in Example 5 was 1:0.2:1 (mass ratio). A humidity sensor was produced in the same manner as in Example 1.
[0048] [Example 8] Cellulose nanofibers (LeoCrysta (registered trademark), fiber diameter 3 nm, fiber length approximately 1000 nm, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were diluted to 1 wt% with ultrapure water, and graphene nanoplatelets (graphene-laminated microplatelets: manufactured by Tokyo Chemical Industry Co., Ltd.) and surfactant (nonionic surfactant Triton TX-100, purchased from Sigma-Aldrich Co., Ltd.) were added to this cellulose nanofiber (1 wt%, 500 mg) solution so that the ratio of cellulose nanofiber: graphene nanoplatelets: surfactant was 1:2:1 (mass ratio), respectively, and the mixture was stirred for 5 minutes and degassed for 2 minutes using a stirring and degassing machine (Thinky Corporation, Mixer AR-100) to prepare resistors (GNP2). A humidity sensor was produced in the same manner as in Example 1.
[0049] [Example 9] A resistor (GNP3) was prepared in the same manner as in Example 8, except that the ratio of the cellulose nanofibers, graphite nanoplatelets, and surfactant in Example 8 was 1:3:1 (mass ratio). A humidity sensor was produced in the same manner as in Example 1.
[0050] [Example 10] A resistor (GNP5) was produced in the same manner as in Example 8, except that the ratio of the cellulose nanofibers, graphite nanoplatelets, and surfactant in Example 8 was 1:5:1 (mass ratio). A humidity sensor was produced in the same manner as in Example 1.
[0051] [Example 11] A resistor (GNP10) was prepared in the same manner as in Example 8, except that the ratio of the cellulose nanofibers, graphite nanoplatelets, and surfactant in Example 8 was 1:10:1 (mass ratio). A humidity sensor was produced in the same manner as in Example 1.
[0052] Among the humidity sensors of Examples 8 to 11, the humidity sensor of Example 8 showed the greatest increase in resistance as the relative humidity (% RH) increased (FIG. 5). [Explanation of symbols]
[0053] 1 Resistor 2 electrodes 3,3' Mask 4. Board 5 Squeegee
Claims
1. A pair of electrodes formed on a substrate; A resistor formed between the pair of electrodes, The resistor contains cellulose nanofibers, carbon particles dispersed among the cellulose nanofibers, and a surfactant; The content of the surfactant is 0.25 to 1 part by mass relative to 1 part by mass of the cellulose nanofiber, The conductive material has electrical conductivity, and the electrical conductivity changes depending on moisture. Humidity sensor.
2. The humidity sensor according to claim 1, characterized in that the content of the carbon particles per 1 part by mass of the cellulose nanofibers is 0.2 to 10 parts by mass.
3. 3. The humidity sensor according to claim 1, wherein the carbon particles are carbon black.
4. The humidity sensor according to any one of claims 1 to 3, characterized in that the cellulose nanofibers have a fiber diameter of 1 to 10 nm and a fiber length of 100 nm to 10 µm.
Citation Information
Patent Citations
Humidity sensitive resistor
JP1984114452A
Dew condensation sensor and method for manufacturing the same
JP2006275997A
Conductive complex
JP2013211108A
Humidity sensor and manufacturing method therefor
JP2019066427A
Inkjet ink
JP2021031536A